Pilot Study of iPS-Derived Neural Cells to Examine Biologic Effects of Alcohol on Human Neurons In Vitro - Lieberman, Richard; Levine, Eric S.; Kranzler, Henry R.; Abreu, Christine; Covault, Jonathan (Alcoholism, clinical and experimental research, 2012)
Background Studies of the effects of alcohol on N‐methyl‐d‐aspartate (NMDA) receptor function and gene expression have depended on rodent or postmortem human brain models. Ideally, the effects of alcohol might better be examined in living neural tissue derived from human subjects. In this study, we used new technologies to reprogram human subject‐specific tissue into pluripotent cell colonies and generate human neural cultures as a model system to examine the molecular actions of alcohol. Methods Induced pluripotent stem (iPS) cells were generated from skin biopsies taken from 7 individuals, 4 alcohol‐dependent subjects, and 3 social drinkers. We differentiated the iPS cells into neural cultures and characterized them by immunocytochemistry using antibodies for the neuronal marker beta‐III tubulin, glial marker s100β, and synaptic marker synpasin‐1. Electrophysiology was performed to characterize the iPS‐derived neurons and to measure the effects of acute alcohol exposure on the NMDA receptor response in chronically alcohol exposed and nonexposed neural cultures from 1 nonalcoholic. Finally, we examined changes in mRNA expression of the NMDA receptor subunit genes GRIN1, GRIN2A, GRIN2B, and GRIN2D after 7 days of alcohol exposure and after 24‐hour withdrawal from chronic alcohol exposure. Results Immunocytochemistry revealed positive staining for neuronal, glial, and synaptic markers. iPS‐derived neurons displayed spontaneous electrical properties and functional ionotropic receptors. Acute alcohol exposure significantly attenuated the NMDA response, an effect that was not observed after 7 days of chronic alcohol exposure. After 7 days of chronic alcohol exposure, there were significant increases in mRNA expression of GRIN1, GRIN2A, and GRIN2D in cultures derived from alcoholic subjects but not in cultures derived from nonalcoholics. Conclusions These findings support the potential utility of human iPS‐derived neural cultures as in vitro models to examine the molecular actions of alcohol on human neural cells.